Pedogenic carbonate nodule δ¹⁸O and δ¹³C record from the Pliocene-Pleistocene Villalba-Alta section, Teruel - Czwakiel, Nicole; Gallagher, Timothy M; Serach, Lily; Ludvigson, Greg; Gao, Peng; Nie, Junsheng; Suc, Jean-Pierre; Da, Jiawei; Breecker, Daniel O (PANGAEA, 2025)
Two sampling campaigns to the Teruel Basin, Spain were carried out in 2016 and in 2019. During the 2016 pilot expedition, 52 nodules (2-6 nodules per stratigraphic level) were collected and the section was measured as depth below the prominent cliff-forming conglomerate at the top of the section. During the 2019 expedition the section was measured as height above the lowest outcrop. 3-14 nodules were collected from each stratigraphic level at which nodules were observed resulting in 1,257 discrete soil carbonate nodules from 148 different heights. 312 nodules from 43 different heights were selected for stable isotope analyses. In the laboratory, nodules were split in half using a mallet and then the micrite was sampled with a Dremel drill avoiding spar. The resulting powders were then reacted with H₃PO₄ under 70°C to liberate CO₂ before being analyzed on a Thermo 253 isotope ratio mass spectrometer operating in continuous flow mode and interfaced with a Thermo Gasbench II at the University of Texas at Austin. Drift corrections were applied to the soil carbonate δ values using an internal Carrara marble (UTM) standard while laboratory standards NBS-18, NBS-19 were used to calibrate delta values to the PDB scale. The standards across all runs had an average reproducibility of 0.16‰. Additionally, spar and coexisting micrite from seven nodules were sampled separately, and analyzed using the same procedure to determine if they had δ¹⁸O values distinct from each other.
Keywords: Northern Hemisphere glaciation; Oxygen and carbon stable isotopes; Pliocene; soil carbonate